(untitled) (Czech Journal of Multidisciplinary Innovations, 2023)
Spending is an instinctive, biological behavior and an important aspect of the activities that the state performs towards its citizens, as it represents the face of the state’s authority, and it was revealed through research the depth of the relationship between gross domestic product and spending in all its forms, and this is shown by the work of the multiplier in the economy, but in the Iraqi economy the volume of spending does not affect the The multiplier in the economy as well as the effect of the accelerator on economic activity. The study dealt with consumer spending in the Iraqi economy and the nature of investment spending during the study period, by relying on the extractive sector and its significant role in the gross domestic product. And debt, through the standard model, it was found that there is a long-term balance between the gross domestic product and public spending and other variables in the model, and the study concluded that the dependence of the gross domestic product on the extractive sector in generating revenues was not the result of the interaction between the economic sectors and the generation of added value.